SOSIALISASI PEMANFAATAN QR CODE UNTUK PENINGKATAN KEAMANAN DALAM TRANSAKSI KEUANGAN DIGITAL PADA SISWA SMA - Yolanda Safitri Nelaz; Sisi Hendriani; Afifah Cahayani Adha (LPPM Universitas Awal Bros, 2026)
The Quick Response Code Indonesian Standard (QRIS) is a QR Code payment standard for Indonesian payment systems developed by Bank Indonesia and the Indonesian Payment Systems Association (ASPI). Digital transformation itself means the comprehensive expansion of strategies, operations, processes, methodologies, business practices, and talent, all of which are combined to deliver more efficient and cost-effective results. The various benefits and objectives of financial digitization still have loopholes for crime. Digital crime also occurs in the use of financial applications in fintech, activities or financial transactions that previously had to be paid for using cash, can now be done easily with financial wallet applications / e-wallets often known as Dana, Shopeepay, Gopay and many more. Many students do not fully understand available security mechanisms, such as two-factor authentication, making them vulnerable to the risk of fraud. Younger age groups tend to ignore security protocols because they prioritize practicality. Community Service activities were carried out at SMAN Olahraga Pekanbaru.